2018
DOI: 10.1002/acp.3384
|View full text |Cite
|
Sign up to set email alerts
|

The role of intonation for interrogative suggestibility

Abstract: SummaryThe detrimental consequences of suggestive witness manipulation have been frequently discussed in the literature. Notably, these discussions have been limited to the consequences of suggestive question types and interrogator conduct. This study is the first to investigate the influence of interrogator's intonation on interrogative suggestibility. Specifically, utilizing a modified German version of the forensic Gudjonsson suggestibility scale as dependent variable, we experimentally manipulated phrase-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 32 publications
0
11
1
Order By: Relevance
“…In order to gauge the potential influence of intonation during interrogation, participants’ memory performance needed to be ascertained. To this end, we employed the German version of the GSS-1, the forensically relevant version of the GSS (GGSS-1; [4]) consisting of a short story of a robbery broken down into 40 distinct items (Table 2). The Kiel University Institute of Phonetics and Digital Speech Processing produced a high-quality digital natural voice recording of four versions of the GGSS-1 story that differed with respect to their pitch curve and/or the auditive prominence of a few words but not in content.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In order to gauge the potential influence of intonation during interrogation, participants’ memory performance needed to be ascertained. To this end, we employed the German version of the GSS-1, the forensically relevant version of the GSS (GGSS-1; [4]) consisting of a short story of a robbery broken down into 40 distinct items (Table 2). The Kiel University Institute of Phonetics and Digital Speech Processing produced a high-quality digital natural voice recording of four versions of the GGSS-1 story that differed with respect to their pitch curve and/or the auditive prominence of a few words but not in content.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, from a legal psychological perspective, it has been only recently demonstrated that phrase-falling intonations (indicating claims/facts rather than questions) on the interrogator’s side contributed to increased interrogative suggestibility (i.e. “the extent to which, within a closed social interaction, people come to accept messages communicated during formal questioning, as the result of which their subsequent behavioral response is affected”[3], p. 84) in interviewed participants during the recall phase of more complex verbal information [4]. However, it remains an open empirical question whether the influence of intonation comes into effect as early as in the encoding phase of verbally presented episodes.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations